1977
DOI: 10.1161/01.cir.56.6.1024
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of left ventricular function from multiple gated acquisition cardiac blood pool imaging. Comparison to contrast angiography.

Abstract: Global ventricular function was evaluated by both multiple gated cardiac blood pool scans (MUGA) and contrast ventriculograms in a group of 17 patients with suspected coronary artery disease. The contrast ventriculograms were analyzed frame by frame to generate a volume versus time curve for each patient, while the tracer data were analyzed by two methods: 1) the standard method, in which the left ventricle is identified on the end-diastolic frame and the background corrected activity under the region of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(33 citation statements)
references
References 6 publications
0
32
0
1
Order By: Relevance
“…Radionuclide ejection fraction was determined in the left anterior oblique view that gave the best separation between the right and left ventricles and was calculated by standard computerized techniques. 13 Exclusion criteria. Patients were ineligible for the study if they had (1) symptomatic VPBs or ventricular tachycardia with 10 beats or more in a row; (2) persistent second-or third-degree heart block; (3) advanced life-threatening diseases of other organ systems, such as uremia, advanced respiratory disease, cancer or liver failure; (4) complications such as stroke or thromboembolism that required prolonged hospitalization; (5) previously documented hypersensitivity or intolerance to aprindine; or if they (6) were previously treated with membraneactive antiarrhythmic agents such as quinidine, procainamide, or phenytoin; (7) Administration of study drug.…”
Section: Methodsmentioning
confidence: 99%
“…Radionuclide ejection fraction was determined in the left anterior oblique view that gave the best separation between the right and left ventricles and was calculated by standard computerized techniques. 13 Exclusion criteria. Patients were ineligible for the study if they had (1) symptomatic VPBs or ventricular tachycardia with 10 beats or more in a row; (2) persistent second-or third-degree heart block; (3) advanced life-threatening diseases of other organ systems, such as uremia, advanced respiratory disease, cancer or liver failure; (4) complications such as stroke or thromboembolism that required prolonged hospitalization; (5) previously documented hypersensitivity or intolerance to aprindine; or if they (6) were previously treated with membraneactive antiarrhythmic agents such as quinidine, procainamide, or phenytoin; (7) Administration of study drug.…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of the RVG method for determining LVEF has previously been evaluated and these studies indicate excellent correlations compared to other methods such as contrast angiography. [31][32][33][34][35] Wackers et al 34 found a 1.4% (Ϯ1.2) and 1.6% (Ϯ1.4) variability for intraand interobserver RVG measurements, respectively. In the same study, variations between examinations performed on the same day and on separate days were 3.3% (Ϯ3.1%) and 4.3 (Ϯ3.1%), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Radionuclide blood pool imaging is one noninvasive diagnostic method for measurement of LVEF. Correlation between radionuclide and contrast angiographic LVEFs is not perfect, however; in general, radionuclide LVEFs are slightly lower than contrast angiographic LVEFs.4O 41 Second, mathematic models developed here identify high-and low-risk patient groups based on factors defined in the first hours of acute myocardial infarction and illustrate the impact of interventional therapies given 3.5 to 6.0 hr after onset of the event.…”
Section: Methodsmentioning
confidence: 95%